L’approccio cognitivista e la coniazione di parole nuove in italiano — alcune riflessioni teoriche - Godzich, Anna (Neophilologica, 2019)
The paper investigates the cognitive approach to word formation in present-day Italian within a larger overview of lexical creativity and users’ competence. Various accounts of lexical creativity are reviewed. The aim of this work is to show the importance of changing cultural needs in word formation with a deeper insight into compounding. Moreover, the author emphasizes the fact that both lexicon and syntax are creative.